Unique Presentation of Akinetic Mutism and Coexisting Thyroid Storm Relating to Stroke - Mohankumar Kurukumbi; Thao Dang; Najeeb Crossley; Alice Esame; Annapurni Jayam-Trouth (Case Reports in Neurological Medicine)
Akinetic mutism is described in various clinical presentations but typically is defined as a state wherein the patient appears awake but does not move or speak. It can be divided into two different subtypes; the most common subtypes depend on the lesion location, mesencephalic-diencephalic region, also called apathetic akinetic mutism (somnolent mutism), and those involving the anterior cingulate gyrus and adjacent frontal lobes called hyperpathic akinetic mutism. The pathway of akinetic mutism is believed to originate from circuits that link the frontal and subcortical structures. This case reports a 48-year-old African American female with bilateral anterior cerebral artery stroke and akinetic mutism with coexisting thyroid storm. This patient with bilateral anterior cerebral artery infarcts presented with characteristics that are typical for akinetic mutism such as having intact eye movements but an inability to respond to auditory or visual commands. With the incidence of bilateral anterior cerebral artery (ACA) ischemic stroke being rare and the incidence of akinetic mutism secondary to ischemic stroke even rarer, we suspect that this patient potentially had a unilateral occlusion of anomalous anterior cerebral vasculature.